Learning Analytics for monitoring and analyzing student’s careers at University - Robasto, Daniela (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
After a preliminary analysis on the concept of Leaning Analytics and its necessary interconnections with Big Data and Business Intelligence in the academic field, the paper presents the first steps of a pilot project at the University of Parma. The pilot project, being tested, is aimed at using Learning Analytics in order to lead to informed and strategic choices regarding: 1) an enhancement of guidance actions in itinere more calibrated on the type of problematic and not distributed "in the rain" ; 2) the possible redesign of the study plans of the CdS subject to analysis and the planning of possible preparatory courses between courses; 3) the early identification of “complex / problematic” courses) the design of specific teacher training seminars on teaching and docimological skills, starting from real data on student careers and contextualised by disciplinary sectors. The contribution is given as an example the “screens” of a DEMO that is under construction and experimentation at the CdS of Informatica UNIPR and which is considered as an example for the impact in terms of usability of the information for different types of stakeholders. The work ends by emphasizing the possible effects of pedagogical research on LA, in the view of consolidation of the self-assessment and improvement processes of Italian universities.